An experimental investigation on the drying characteristics and kinetics of Baorixile lignite in a fixed bed. (1st October 2019) - Xu, Ying; Qin, Xiaowei; Zhang, Guojie; Zhang, Yongfa
Highlights: An independently developed fixed bed drying reactor with fine airtightness was used. Drying characteristics of isothermal and Non-isothermal process were discussed. The dehydration rate has a certain correlation with different atomic ratio in the isothermal drying process. Kinetics of non-isothermal characteristics during lignite drying process was presented. The pores of 20–56 nm played an important role to total pore volume during the drying process of lignite. Abstract: This study investigates the effects of drying treatment on coal composition, function groups, pore structure, and drying characteristics of Baorixile lignite in an independently developed fixed bed with high sealing performance. The variation of functional groups of lignite during the drying process is determined by Fourier Transform Infrared spectroscopy and chemical quantitative analytical method, the pore structure is analyzed by Scanning Electron Microscope and nitrogen adsorption, and the drying characteristics is discussed by using isothermal and Non-isothermal method, respectively. The results show that the dehydration rate has a significant linear correlation with the atomic ratio (H/C + O/C) in the isothermal drying process of lignite. The dehydrating characteristics at different temperatures and different time periods indicate there are three stages in isothermal drying process. Two different dynamic models are evaluated for the kinetic equation in non-isothermal process, and the results show that Dolye method was more agree with experimental data. The continuous increasing of pore size causes to the decreasing of the specific surface, and the pore volume was mainly contributed by the pores of 20–56 nm during the drying process of lignite.